Plan de desarrollo y ordenamiento territorial de la parroquia San Lucas perteneciente al cantón Loja. - Jaramillo Romero, Juan Pablo (2011)
This research paper focuses the use of Geographic Information Systems (GIS) applied to the development of the Development Plan and Spatial Planning of the parish of San Lucas, Loja belonging to the canton. With this perspective, carried out a diagnostic process, based on which a proposal was raised and land development. Was taken as a starting point, the precise analysis of eco-environmental systems, economic, human settlements, socio-cultural, mobility and connectivity, and land management. All these systems were broken down and studied each of their natural and human components. With the help of Geographic Information Systems, processed in digital form each of the variables analyzed for overlaying thematic maps and get the final map showing the current model of the territory. From knowing the main problems and potential and make the FODA analysis, it devised a development proposal and land, the same is directed to appropriate use of natural components of the parish and the proper use of the territory. Theyraisedtheirrespective objectives and guidelines for each system, based on their weaknesses and greatest strengths. In each guideline projects were established, noting the government entity will be responsible for implementing these projects. To manage these projects was set up a committee to be composed of the leading authorities of the parish and planning agencies in the region. The information obtained in digital and analog form the basis for Decentralized Autonomous Government of San Lucas, to somehow contribute to the development of the parish and the correct use of territory, gender affect the environment, hence the parish become a model of sustainable development for the region and country.